Electromagnetic wave scattering by a thin layer in which many small particles are embedded - Ramm, Alexander G. (My University, 2010)
Scattering of electromagnetic (EM) waves by many small particles (bodies), embedded in a thin layer, is studied. Physical properties of the particles are described by their boundary impedances. The thin layer of depth of the order O(a), with many embedded small particles of characteristic size a, is described by a boundary condition on the surface of the layer. The limiting interface boundary condition is obtained for the effective EM field in the limiting medium, in the limit a -- 0, where the number M(a) of the particles tends to infinity at a suitable rate.
Keywords: Electromagnetic wave scattering; Thin layer; Small particles; Boundary impedance